The invisibility of the church for Luther and Calvin - McKenzie, Peter R. (The University of Edinburgh, 1953)
The development that lies in the thought of Luther and Calvin on the nature of the church is within a basic unity. In attempting a comparison of their conceptions of the invisibility of the church it is assumed that the great¬ est weight is to be laid upon their mature views, while taking into account the earlier developments. This means in the case of Luther that less emphasis is to be given to the sharp opposition of the church as an invisible communio to the visible structure of Rome, during the earlier years 1518-20, and more to the final view of the church as hidden, and made visible only in the signs of Word and sacraments. For Calvin, it means that the fully developed double-line view of the church as the invisible elect, and as visibly realised, united in the conception of the Christ-community, is to be taken as the mature view, and less importance given to earlier views where this double-line was not brought out so clearly.

In the comparison that follows a number of loci are selected to indicate something of the fullness that for both men lay behind their conception of the invisibility of the church:

The invisibility of the church meant, first of all, the church placed under the Lordship of Christ, as such, it was invisible, whereas ruled by men it assumed a false visibility. The church has no earthly head. Luther maintained this at the outset, to the point where he could not see any extensive ecclesiastical authority. And throughout he held that Christ alone ruled his church through the preached Word and sacraments. Calvin went a stage further by making Christ's sovereignty a constitutional principle: i.e. he allowed no constitutional provision for a single earthly head or ruler. His ground was that such rulers can and do tear the Body of the church away from its risen head. Under the principle of cuius regie ejus religio, precisely this happened. Political rulers determined the mode of religion for their subjects.